Agricultural Marketing Strategies In The Digital Era: Improving The Competitiveness Of Local Products - Gumoyo Mumpuni Ningsih; Harun Rasyid; Natali Ningsih; Darminto Pujotomo; Gijanto Purbo Suseno (Al-Makki Publisher, 2024)
In the digital era, the marketing of local agricultural products faces new challenges and opportunities, necessitating innovative strategies to enhance competitiveness. This study aims to identify effective agricultural marketing strategies to improve the competitiveness of local products in the digital market. A qualitative research method with a case study approach was employed, involving in-depth interviews with agricultural entrepreneurs and secondary data analysis from various digital platforms. The findings reveal that the use of digital technology, such as social media and e-commerce, and the adoption of data-driven marketing practices play a significant role in expanding market reach and boosting sales. The most effective strategies involve a combination of product storytelling, content personalization, and direct consumer engagement. The study concludes by highlighting the importance of integrating digital technology into marketing strategies to strengthen the position of local agricultural products in the global market and the need to enhance the capacity of entrepreneurs to utilize this technology optimally.